(untitled) (Pakistan Journal of Science, 2022)
Periplaneta americana (cockroach) are the carriers of all sorts of pathogens and pose great public health risks. Present study was aimed to check the response of bacteria isolated from external surface (CXA2 and CXA3) and rectum part (CIA1, CIA2, CIA3) of Periplaneta americana (captured from kitchen sewerage) towards biofilm formation and auto aggregation. Both these parameters are the prerequisite characteristics for establishing pathogenicity of any bacteria. Bacterial isolates showed diverse morphology and biochemical characteristics. Biofilm at shaking and non-shaking conditions was quantified and found highest at non-shaking conditions in CIA3 as compared to rest of bacterial isolates. Among all isolates, auto aggregation in CIA3 showed 143 % while 196 % in CXA2 as compared to rest of bacterial isolates at 3rd hour (at 37◦C) of culture incubation. Results showed that biofilm and cell aggregation of microbes helped them to colonize abiotic surfaces that result in bacterial infection. Therefore, cleaning practices should be the cohesive part of domestic routines to remove the carrier pests i.e., cockroaches as well as bacteria.